Simulation modeling of tool delivery system in a machining line - Tjahjono, Benny; Ladbrook, J. (IEEE, 2011)
This paper describes an industrial project aiming to enhance the existing simulation modeling suites used at a car engine factory in the UK. The company continues to enhance its simulation modeling capabilities towards so called the `total plant modeling' which not only covers the production facilities but also key ancillary facilities. Tool delivery is one such ancillary process. The existing modeling practices at the company are limited to modeling tool changes and assume that tools meet their expected life and the replacement is always available. In reality, the tools are not always reaching the expected life, the facilities in the tool crib are a limiting resource and the tool inventory has to be minimized. The tool delivery system developed in this project has specific features that model how the tool crib operates, how tools are supplied to the machining lines and various operating strategies
Keywords: Computer numerical control; Integrated circuit modeling; Machining; Manufacturing; Production facilities; Vehicles